Investigation of Simulated Domestic Sewage Treatment Performance Via Scenedesmus quadricauda and Chlorella pyrenoidosa - Chao LI; Xiaomei HUI; Zihe PAN; Yachuan WU; Biao FAN (Taiyuan Ligong Daxue xuebao, 2021)
The fast development of urbanization emits huge amount of domestic wastewater, of which the high contents of chemical oxygen demand(COD), NH4-N, total nitrogen and phosphorous lead to the difficulty in their complete removal and the recycling of the water. To solve this problem, the simulated domestic sewage treatment efficiency was investigated via scenedesmus quadricauda and chlorella pyrenoidosa in terms of COD, NH4-N, total nitrogen (TN), and total phosphorous (TP). The influence of the dosage of the two microalgae (100 mg/L and 200 mg/L) on wastewater treatment and the relationship of the indexes COD, NH4-N, TN, and TP with handling time were examined. The surface morphology and chemistry before and after water treatment were characterized through SEM and FTIR, respectively. Scenedesmus quadricauda and chlorella pyrenoidosa show significant removal efficiency towards COD, with removal rates of 77.92% and 80.43%, respectively. Chlorella pyrenoidosa shows better NH4-N (58.34%) and TP (51.09%) removal efficiency than scenedesmus quadricauda for NH4-N (43.66%) and TP (41.52%). Scenedesmus quadricauda shows better TN removal efficiency (78.33%) than chlorella pyrenoidosa (76.67%). The results might provide fundamental and technical support for the application of algal microorganism.